2020
DOI: 10.1002/pc.25885
|View full text |Cite
|
Sign up to set email alerts
|

Central tearing behavior of PVDF coated fabrics with multiple initial notches

Abstract: Tear failure is an essential issue for membrane structures, but always ignored in the current design specifications or codes. This paper presents the central tearing behaviors of PVDF coated fabrics with initial notches. Then, the influence of notches number, notches length, and notches orientation were considered. Finally, the tearing mechanisms under multiple initial notches were systematically studied. The results show that the strength of PVDF coated fabrics is significantly affected by the parameters of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Xu et al [ 55 ] described the puncture resistance behaviors of architectural coated fabric and its influence on the effects of boundary condition, penetrator shape, yarns angle, puncture rate, the weight percentage of fiber, and coating on puncture resistance behaviors of coated fabric. Li et al [ 56 ] described the central tearing behaviors of PVDF coated fabrics with initial notches under the influence of notches number, notches length, and notches orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [ 55 ] described the puncture resistance behaviors of architectural coated fabric and its influence on the effects of boundary condition, penetrator shape, yarns angle, puncture rate, the weight percentage of fiber, and coating on puncture resistance behaviors of coated fabric. Li et al [ 56 ] described the central tearing behaviors of PVDF coated fabrics with initial notches under the influence of notches number, notches length, and notches orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the boundary was set as the same as the experiment, and the tension force was generated using the temperature method. The temperature value was calculated as shown in Equation (1).…”
Section: The Simulation Including Airmentioning
confidence: 99%
“…Prestressed membrane structures are widely used by architects due to their beautiful shape, small ratio of weight over strength and other advantages [1][2][3]. Being different to traditional structures, their stiffness is mainly provided by tension force and geometry curvature, which leads to prestressed membrane structures being very sensitive to dynamic loads, such as wind, rain, hail and other loads [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Li etal. 23 have studied the central tearing behavior of PVDF. They found that the failure mode of tearing depended on the initial notches.…”
Section: Introductionmentioning
confidence: 99%